Synthesis of TiO2/Carbon Nanoparticle (C-dot) Composites as Active Catalysts for Photodegradation of Persistent Organic Pollutant - Dedri Syafei; Sri Sugiarti; Noviyan Darmawan; Mohammad Khotib (Universitas Gadjah Mada, 2017)
TiO2/C-dot composites were synthesised by sol-gel method and investigated as catalysts for photocatalytic degradation of persistent organic pollutants (perchloroethylene, PCE). The composites photoluminescence properties was shown by visual analysis and the synthesis product was characterized by XRD, FTIR, fluorescence spectrophotometer, and UV-Vis spectrophotometer. Degradation of PCE 0.1% (v/v) in the aqueous phase was investigated under sunlight irradiation for 2 h. Photodegrade efficiency of PCE was determined by GC. Composites of TiO2/C-dot 2.5% (w/w) was succesfully to degrade PCE under sunlight irradiation and its photodegrade efficiency was up to 89.45%.